The use of virtual reality in education - Mauri Medrano, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Recent technological developments in the field of teaching have brought significant changes in the daily practice of teaching. Due to the great development of computer resources, we must adapt the old and traditional teaching methods to the new technological conditions existing in our social environment. One of the latest developments in the field of education are the virtual reality techniques, which will change the course of our educational systems in few years. This transformation is currently present in the technologically advanced countries.

Dokonujący się rozwój technologiczny przyniósł znaczne zmiany w codziennej praktyce edukacyjnej. Z powodu ogromnego postępu w zakresie zasobów komputerowych, jesteśmy zmuszeni do zaadaptowania dotychczasowych, tradycyjnych metod nauczania do nowych warunków technologicznych, występujących w środowisku społecznym. Jednym z ostatnich osiągnięć w dziedzinie edukacji są techniki wirtualnej rzeczywistości, które w ciągu kilku lat wymuszą dalsze zmiany naszych systemów edukacyjnych. Z technikami tymi mamy już dziś do czynienia w zaawansowanych technologicznie krajach.
Wykorzystanie wirtualnej rzeczywistości w edukacji
Keywords: virtual reality; education; learning; simulation; wirtualna rzeczywistość; edukacja; nauka; symulacja